Type 2 diabetes mellitus and higher rate of complete atrioventricular block: a Danish Nationwide Registry. (26th November 2022) - Haxha, Saranda; Halili, Andrim; Malmborg, Morten; Pedersen-Bjergaard, Ulrik; Philbert, Berit T; Lindhardt, Tommi B; Hoejberg, Soeren; Schjerning, Anne-Marie; Ruwald, Martin H; Gislason, Gunnar H; Torp-Pedersen, Christian; Bang, Casper N
Abstract: Aims: The present study aimed to determine the association between Type 2 diabetes mellitus (T2DM) and third-degree (complete) atrioventricular block. Methods and results: This nationwide nested case–control study included patients older than 18 years, diagnosed with third-degree atrioventricular block between 1 July 1995 and 31 December 2018. Data on medication, comorbidity, and outcomes were collected from Danish registries. Five controls, from the risk set of each case of third-degree atrioventricular block, were matched on age and sex to fit a Cox regression model with time-dependent exposure and time-dependent covariates. Subgroup analysis was conducted with Cox regression models for each subgroup. We located 25 995 cases with third-degree atrioventricular block that were matched with 130 004 controls. The mean age was 76 years and 62% were male. Cases had more T2DM (21% vs. 11%), hypertension (69% vs. 50%), atrial fibrillation (25% vs. 10%), heart failure (20% vs. 6.3%), and myocardial infarction (19% vs. 9.2%), compared with the control group. In Cox regression analysis, adjusting for comorbidities and atrioventricular nodal blocking agents, T2DM was significantly associated with third-degree atrioventricular block (hazard ratio: 1.63, 95% confidence interval: 1.57–1.69). The association remained in several subgroup analyses of diseases also suspected to be associated with third-degree atrioventricular block. There was a significant interaction with comorbidities of interest including hypertension, atrial fibrillation, heart failure, and myocardial infarction. Conclusion: In this nationwide study, T2DM was associated with a higher rate of third-degree atrioventricular block compared with matched controls. The association remained independent of atrioventricular nodal blocking agents and other comorbidities known to be associated with third-degree atrioventricular block. Structured Graphical Abstract: Structured Graphical Abstract Graphical summary of the method and main findings of the present study. HR, hazard ratio T2DM, Type 2 diabetes mellitus